Optimization of the prevention of perinatal pathology in women with gestational endotheliopathy - D.H. Konkov; S.М. Kosianenko; R.S. Ostreniuk; O.L. Lovkina (Publishing House TRILIST, 2022)
Objectives: to evaluate the clinical effectiveness of the Metida for the prevention of perinatal pathology in pregnant women with gestational endotheliopathy and with the risk of preeclampsia. Materials and methods. 68 pregnant women with verified gestational endotheliopathy and with risk of preeclampsia > 1:150 participated in a prospective clinical comparative study. The patients were divided into subgroups: the first subgroup included 30 women who from 11-13 weeks of pregnancy received acetylsalicylic acid 100 mg/day and vitamin D 2000 IU/day; the II subgroup included 38 pregnant women who from 11-13 weeks of gestation received acetylsalicylic acid 100 mg/day, vitamin D 2000 IU/day and Metida (300 mg of elemental magnesium, 30 mg of vitamin B6). 28 practically healthy pregnant women of the control group received vitamin D 1000 IU/day. The clinical effectiveness of therapy was evaluated by comparing the number of cases of perinatal pathology; cases of intrauterine suffering of the fetus; the dynamics of indicators of laboratory-instrumental research methods (markers of the risk of perinatal pathology) and the pregnancy outcomes. Results. Metida as an additional preventive therapy made it possible to significantly reduce the number of cases of placental dysfunction (р = 0.01) and intrauterine suffering of the fetus (р = 0.02) compared to standard preventive therapy. There was also a 6-fold reduction in the incidence of preeclampsia and premature birth due to magnesium supplementation, compared to pregnant women who received only acetylsalicylic acid and vitamin D. There was a significant decrease in serum indicators of markers of endothelial dysfunction in women with gestational endotheliopathy as a result of taking magnesium: vascular endothelial growth factor (p < 0.00001), endoglin (p < 0.00001) compared to patients who did not receive magnesium, and there was also normalization of the of 25(OH)D level in blood serum compared to the control group (p = 0.33). Conclusions. Additional Mg supplementation during pregnancy may reduce the likelihood of perinatal pathology in high-risk patients and help normalize serum markers of endothelial dysfunction in women with high risk of preeclampsia.